Understanding cervical cancer prevention in Africa: a qualitative systematic review of the role of men - Lawrence Doi; Dorcas Obiri-Yeboah; Nancy Innocentia Ebu Enyan; Aigli Raouna; Michelle King-Okoye; Sebastian Ken-Amoah; Patrick Kafui Akakpo (BMJ Open)
Background Cervical cancer (CC) is a preventable noncommunicable disease if detected early through screening for precancers and appropriately managed. The causal link with high-risk human papillomavirus infection is established, making elimination possible through the WHO multipronged 90:70:90 strategy. However, practical CC elimination efforts need to address issues within the sociocultural context that can facilitate or hinder prevention strategies. In this regard, the role of men in promoting reproductive health, especially in Africa, cannot be overemphasised.Objective This systematic review examined the extent of involvement of men in CC prevention in Africa and its impact on the WHO CC elimination strategy.Methods A comprehensive search for relevant literature was conducted from 2008 to 2023 in the following electronic databases: Embase, Medline, Global Health, APA PsycINFO, Scopus, Web of Science, CINAHL Plus and the WHO website. Eligible studies explored the views of n=592 men. Screening of abstracts and titles, data extraction and quality assessment were performed in duplicate. A narrative synthesis was performed, as developed by the Economic and Social Research Council Methods Programme, to synthesise the qualitative data.Results Out of the 1961 studies identified through the electronic database search, 16 met all inclusion criteria. This review revealed varying levels of awareness of CC among men; while some had little to no knowledge, others demonstrated a comprehensive understanding. Gaps in knowledge and perception of CC were evident across studies. Both individual and systemic challenges shaped the perspectives of men on screening as a preventive measure, resulting in a range of attitudes and concerns regarding human papillomavirus vaccination. Though male participation in CC prevention was generally low, it was noted that males were willing to play an active role in CC screening and vaccination by supporting the process. Men believed that aggressive education and awareness creation among men were required.Conclusions This review highlights the need for targeted interventions to improve awareness, knowledge and perception of CC among men. Such efforts are essential to help men recognise their crucial role in supporting CC elimination within the African context.PROSPERO registration number The review protocol was registered on 26 June 2023 in PROSPERO with registration number CRD42023437100.